Pengaruh Work Life Balance Dan Stres Kerja Terhadap Kepuasan Kerja Pada Karyawan Bank Nagari Cabang Utama Padang - Ikhsan Syeftian; Alvin Alfian (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the effect of Work Life Balance and work stress on job satisfaction of Bank Nagari Main Branch Padang employees. The population in this study were all employees of Bank Nagari Main Branch Padang totaling 183 people. The sample in this study was 122 people. This study is a quantitative study. The instrument used in this study was a questionnaire. The results of the study using multiple linear regression analysis showed that simultaneously there was an effect of Work Life Balance and work stress on job satisfaction and partially Work Life Balance had a positive effect on job satisfaction, partially work stress had a positive effect on job satisfaction